Coincidence Points for Expansive Mappings under c-Distance in Cone Metric Spaces - Hassen Aydi; Erdal Karapınar; Sirous Moradi (International Journal of Mathematics and Mathematical Sciences)
We establish some fixed (common fixed) and coincidence point results for mappings verifying some expansive type contractions in cone metric spaces with the help of the concept of a c-distance. Our results generalize, extend, and unify several well-known comparable results in the literature. Some examples are also presented.